PERAN DAN INTERAKSI ANTAR AKTOR DALAM PENGEMBANGAN DESA WISATA KEMBANGARUM, DESA DONOKERTO, KABUPATEN SLEMAN - , MUHAMMAD IMAM FUADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In 2009, tourism has become the biggest source of revenue for the district of Sleman, and gradually continued to increase in subsequent years. Nowadays, nature-based tourism to be one excellent for tourists. As a result, now the actors, especially the nature-based tourism continue to make improvements in order to compete in attracting tourists. One that still exist and possibly to continue to be developed in Sleman district is a tourist village. Desa Wisata Kembangarum is one of the tourist village located in the district of Sleman and quite successful. This is proven with the number of awards they have acquired. In this research, Desa Wisata Kembangarum become the main locus. Which this tourist village is initiated and maintained by a third party, Sanggar Pratista. With managed by a third party, of course, will raises the question of how the roles and interactions that occur between actors in the development activities. This study used qualitative methods to answer the research questions. While the data collection is done by conducting interviews of the actors involved. In addition to getting information from primary sources, this research was also supported by secondary sources such as documents to be able to answer the research question with better. The results of the research that has been conducted shows that the characteristic of the interactions that occur between actors is cooperative. In addition, the results also showed that there are two categories of patterns of interaction between actors. First, just between the actors and Sanggar Pratista as manager